Unveiling the therapeutic potential of Lobaria extract and its depsides/depsidones in combatting Aβ42 peptides aggregation and neurotoxicity in Alzheimer’s disease - Yang, Meixia; Yan, Caishan; Ospondpant, Dusadee; Wang, Lisong; Lin, Shengying; Tang, Wai Lun; Dong, Tina Tingxia; Tong, Penger; Xu, Qin; Tsim, Karl Wah Keung (Frontiers in Pharmacology, 2024)
Background: The development of effective inhibitors that can inhibit amyloid β (Aβ) peptides aggregation and promote neurite outgrowth is crucial for the possible treatment of Alzheimer’s disease (AD). Lobaria (Schreb.) Hoffm., a traditional Chinese medicine used in Himalaya region for inflammatory diseases, contains depsides/depsidones (DEPs) such as gyrophoric acid, norstictic acid, and stictic acid known for their anti-cancer and anti-inflammation properties. Methods:Lobaria extracts were analyzed using HPLC to identify DEPs and establish standards. The inhibitory effects of Lobaria on Aβ42 fibrillization and depolymerization were assessed using various approaches with biophysical and cellular methods. The neuroprotective activity of Lobaria extracts and its DEPs aganist Aβ-mediated cytotoxicity was also evaluated. Results: Norstictic and stictic acid were found in the water extract, while norstictic, stictic, and gyrophoric acid were detected in the ethanol extract of Lobaria. Both extracts, and their DEPs effectively inhibited Aβ42 fibrillation and disaggregate mature Aβ42 fibrils. Notably, the ethanol extract showed superior inhibitory effect compared to the water extract, with gyrophoric acid being the most effective DEPs. Additionally, herbal extract-treated Aβ42 aggregation species significantly protected neuronal cells from Aβ42-induced cell damage and promoted neurite outgrowth. Conclusion: This study is the first to investigate the effect of Lobaria on Aβ42 and neuronal cell in AD. Given that Lobaria is commonly used in ethnic medicine and food with good safety records, our findings propose that Lobaria extracts and DEPs have potential as neuroprotective and therapeutic agents for AD patients.